Anti-Phospholipid Antibodies in Patients Undergoing Total Joint Replacement Surgery. (31st October 2012) - Simpson, Melissa; Sanfelippo, Michael J.; Onitilo, Adedayo A.; Burmester, James K.; Hocking, William; Yale, Steven H.; Mazza, Joseph J.
Abstract : Background . Patients undergoing joint replacement remain at increased risk for venous thromboembolism (VTE) compared to other types of surgery, regardless of thromboprophylactic regimen. The pathophysiologic processes rendering this group of patients at risk for VTE are multifactorial. Procedure-specific and patient-specific exposures play a role in the postoperative development of VTE, including the development of anti-phospholipid antibodies (aPL). Methods . We measured three aPL (anti-cardiolipin, anti-β 2 glycoprotein, and lupus anticoagulant) in 123 subjects undergoing total knee or hip arthroplasty to describe the presence of these antibodies preoperatively and to describe the rate of postoperative seroconversion among those people who were negative preoperatively. Postoperative antibodies were measured at day 7, 14, and 21. Results . The prevalence of aPL antibodies in the preoperative period was 44%, positive subjects were more likely to be smokers (P = 0.05 ) and were less likely to have undergone a previous arthroplasty procedure (P = 0.002 ). Subjects seroconverted in a 21 day postoperative period at a rate of 79%. Conclusions . These pilot data suggest that the prevalence of aPL in this population both preoperatively and postoperatively is higher than previously expected. Further studies are needed to describe aPL in a larger population and to establish their clinical significance in populations undergoing joint replacement surgeries.